2014
DOI: 10.1099/vir.0.064436-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel papillomavirus in Adélie penguin (Pygoscelis adeliae) faeces sampled at the Cape Crozier colony, Antarctica

Abstract: Papillomaviruses are epitheliotropic viruses that have circular dsDNA genomes encapsidated in non-enveloped virions. They have been found to infect a variety of mammals, reptiles and birds, but so far they have not been found in amphibians. Using a next-generation sequencing de novo assembly contig-informed recovery, we cloned and Sanger sequenced the complete genome of a novel papillomavirus from the faecal matter of Adé lie penguins (Pygoscelis adeliae) nesting on Ross Island, Antarctica. The genome had all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 89 publications
0
36
0
Order By: Relevance
“…As highlighted by Varsani et al (2014) for the P. adeliae papillomavirus, we are confident that AdPyV is associated with Adélie penguins and that the chances of contamination by the South Polar skua (Stercorarius maccormicki; preys on Adélie penguin eggs and chicks), the only other bird in the subcolony, are extremely slim; the skua do not nest within the faecal trays, are chased away by the penguins, are outnumbered by the penguins by .200 : 1, and in fact one skua pair defends~1000 nests, and the tray, within its territory. This report expands our current knowledge of the host range of avipolyomaviruses and to the best of our knowledge this is the first report of a polyomavirus associated with penguins.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As highlighted by Varsani et al (2014) for the P. adeliae papillomavirus, we are confident that AdPyV is associated with Adélie penguins and that the chances of contamination by the South Polar skua (Stercorarius maccormicki; preys on Adélie penguin eggs and chicks), the only other bird in the subcolony, are extremely slim; the skua do not nest within the faecal trays, are chased away by the penguins, are outnumbered by the penguins by .200 : 1, and in fact one skua pair defends~1000 nests, and the tray, within its territory. This report expands our current knowledge of the host range of avipolyomaviruses and to the best of our knowledge this is the first report of a polyomavirus associated with penguins.…”
mentioning
confidence: 99%
“…Most of the early studies have relied on serological assays for identifying putative paramyxoviruses, orthomyxoviruses, flavirviruses and birnaviruses in wild penguin populations (Alexander et al, 1989;Austin & Webster, 1993;Gardner et al, 1997;Miller et al, 2010;Morgan et al, , 1985Smith et al, 2008;Thomazelli et al, 2010) and herpesviruses and togaviruses in captive individuals (Kincaid et al, 1988;Tuttle et al, 2005). A handful of recent studies have identified some of the viruses (avipoxviruses, Newcastle disease viruses, adenovirus, avian influenza virus and papillomavirus) at a molecular level (Carulei et al, 2009;Hurt et al, 2014;Kane et al, 2012;Lee et al, 2014;Thomazelli et al, 2010;Varsani et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, sequences related to bovine and human PVs have been found in cats, suggesting cross-species transmission (Egberink et al, 2013). In the last few years, a large number of new PVs have been isolated from faeces/rectal samples of animals (rat, mouse and penguin) (Phan et al, 2011;Shulz et al, 2012;Varsani et al, 2014), particularly following the advent of next-generation DNA sequencing techniques. The risk of contracting HPV diseases for people in close contact with pets and other animals, although not yet demonstrated, cannot be excluded.…”
mentioning
confidence: 99%